Evolution of dispersion in the melt compounding of a model polymer nanocomposite system: A multi-scale study. (July 2019) - Gaspar, Hugo; Santos, Raquel; Teixeira, Paulo; Hilliou, Loic; Weir, Michael P.; Duif, Chris P.; Bouwman, Wim G.; Parnell, Steven R.; King, Stephen M.; Covas, José A.; Bernardo, Gabriel
Abstract: We investigate the morphological development of polystyrene (PS)-C60 nanocomposites along the length of a prototype co-rotating twin-screw extruder with sampling capabilities. The effects of C60 concentration and output on the morphological evolution along the extruder are studied employing a suite of characterization techniques covering a wide range of length-scales, thereby shedding new light on the dispersion mechanism in this model system. We show that the relatively new spin-echo small-angle neutron scattering (SESANS) technique is well suited to probe both the distribution and the dispersion of C60 . SESANS complements optical microscopy (OM) data as it covers sampling areas several orders of magnitude larger than OM. The multi-scale morphological information conveyed by OM, SESANS, SANS and rheological data shows that for larger outputs, C60 agglomerates are eroded as they travel along the extruder, resulting in C60 dispersion and distribution at both molecular and micrometric levels. The picture is more complex when smaller feed rates are used, as the evolution of C60 dispersion depends on the C60 loading. For larger C60 contents, agglomeration develops along the extruder, whereas dispersion is improved for smaller C60 contents. Overall, it is concluded that an over-high feed rate in extrusion does not necessarily result in a bigger size of the nanoparticle agglomerates because of the complex interplay between stresses and residence time. Highlights: The morphological evolution of PS-C60 nanocomposites was studied along the barrel of an extruder with sampling capabilities. The SESANS technique proved well suited to probe both the distribution and the dispersion of C60 in PS nanocomposites. A comparison between the Optical Microscopy and SESANS techniques was performed and their complementary was demonstrated. This is one of the first reports on the application of SESANS to the study of polymer nancomposites.